How do changes in housing prices affect consumer spending? : evidence from Iceland - Anna S. Garðarsd. Blomsterberg 1995- (2022)
Housing is the most predominant component of Icelandic households' wealth. Thus, it is important to understand if fluctuations in the housing market affect consumption and then to what extent. Multiple studies have been conducted on the effect of housing prices on consumption, but this is most likely the first one to study the effect in Iceland. This paper uses a multiple regression analysis to study the effects of changes in housing prices on consumption with real-world card transaction data from the majority of the Icelandic population. Moreover, the study examines if changes in housing prices affect various age cohorts differently. The results indicate that housing prices significantly affect consumption in Iceland, but the effect greatly differs across age groups. The average consumption elasticity was found to be 0.31, which is more elasticity than most previous studies have found. Consistent with the wealth effect theory, the findings showed the greatest elasticity for the older cohorts (40+ years) and the smallest for younger cohorts (16-40 years). Furthermore, the results suggest that increases in housing prices negatively affect younger individuals' consumption, which conflicts with the findings of previous studies from other countries.